Increasing parental participation at school level: a 'citizen to serve' or a 'customer to steer'?. Issue 2 (4th May 2017) - Helgøy, Ingrid; Homme, Anne
ABSTRACT: Collaboration between schools and parents has become increasingly prominent on the political agenda in Norway. Schools are obliged to promote parent–school cooperation in accordance with parents' rights as stakeholders in education. This article explores the governing strategies of seven primary or lower-secondary schools that have taken initiatives to improve parent–school collaboration. The main intention is to explore how New Public Management (NPM) measures (such as market values, decentralization, competition, and output control) and New Public Service (NPS) tools (including coalition building and citizens' involvement) are reproduced at the local level when parent–school collaboration is put on the agenda. The analysis shows that street-level discretion at school level implies considerable uncertainty around the achievement of policy objectives. Different opinions on parents as a target group seem prominent in explaining how frontline workers act and strategize. Two distinct collaboration strategies are identified: serving and steering . The serving strategy is based on a linear partnership by making use of local knowledge in order to reach parents and enable their participation. The steering strategy is characterized by non-linear relationships with parents and certain steering mechanisms by routinizing collaboration activities, modifying goals for parent–school collaboration and rationing school services to parents.